A meta Analysis on the Relationship between Myeloperoxidase G-463A Genetic Polymorphisms and Lung Cancer Susceptibility - Qinghua ZHOU; Hongyu LIU; Shujun LI; Jundong GU; Jing WANG; Feng HUA (Chinese Journal of Lung Cancer, 2010)
Background and objective The relationship between myeloperoxidase G-463A genetic polymorphisms and lung cancer susceptibility has been studied extensively. However, the outcomes are not consistent. The aim of this study is to evaluate the relationship between myeloperoxidase genetic polymorphisms and lung cancer susceptibility by meta analysis. Methods Documents published were retrieved through databases associated with the study. Taking into account the possibilities of heterogeneity of the studies, a statistical test for heterngeneity was performed. The odds ratio and 95%CI were used to evaluate the risks. The meta analysis was applied with RevMan software 4.2, and the forest plot and funnel plot of meta analysis were worked out. Results A total of 5 381 cases and 5 827 controls from studies for Caucasian and a total of 1 558 cases and 1 755 controls from studies for East Asians were included. For Caucasian the pooled OR was 0.91 (95%CI: 0.81-1.02); For East Asians, the pooled OR is 0.83 (95%CI: 0.63-1.09). Publication bias exits in the study for Caucasian, but not for East Asians. Conclusion The results of this study indicated that the polymorphism of myeloperoxidase G-463A was not significantly associated with the lung cancer risk for Caucasian or East Asians. However, further studies for the East Asians is needed for the few subjects.